2015
DOI: 10.1098/rspa.2015.0012
|View full text |Cite
|
Sign up to set email alerts
|

Physical role of topological constraints in localized magnetic relaxation

Abstract: Predicting the final state of turbulent plasma relaxation is an important challenge, both in astrophysical plasmas such as the Sun's corona and in controlled thermonuclear fusion. Recent numerical simulations of plasma relaxation with braided magnetic fields identified the possibility of a novel constraint, arising from the topological degree of the magnetic field-line mapping. This constraint implies that the final relaxed state is drastically different for an initial configuration with topological degree 1 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 23 publications
3
28
0
Order By: Relevance
“…In (b) and (c) there are several observable regions of a particular sign of L f , in particular there are two large regions with a dominant sign L f , one positive one negative, though neither are homogeneous. Whilst it is not the clear splitting into two tubes found in Wilmot-Smith et al (2011), Yeates et al (2015, it is indicative that the tube has not relaxed to a linear force-free state. Unlike the twisted field it is not clear what the effect of reconnection with the background field has had on the distribution.…”
Section: Resulting Relaxationmentioning
confidence: 95%
See 3 more Smart Citations
“…In (b) and (c) there are several observable regions of a particular sign of L f , in particular there are two large regions with a dominant sign L f , one positive one negative, though neither are homogeneous. Whilst it is not the clear splitting into two tubes found in Wilmot-Smith et al (2011), Yeates et al (2015, it is indicative that the tube has not relaxed to a linear force-free state. Unlike the twisted field it is not clear what the effect of reconnection with the background field has had on the distribution.…”
Section: Resulting Relaxationmentioning
confidence: 95%
“…For a linear force-free field j · B = αB · B and L f is just the linear force-free parameter α, which would be constant throughout the domain. This quantity was calculated for relaxing braided and twisted cylindrical fields in Wilmot-Smith et al (2011), Yeates et al (2015. These authors found that a twisted field relaxed to a force-free state with a single sign of α within the tube, although the surrounding background field prevented it from reaching the spatially constant α predicted by the Taylor relaxation hypothesis.…”
Section: Resulting Relaxationmentioning
confidence: 99%
See 2 more Smart Citations
“…A second approach to increasing the complexity of the field is to define fields which partly overlap, creating a composite field with more complex internal topology. This is used in what follows to develop a version of the braided field used in Yeates et al (2010), Wilmot-Smith et al (2011), Yeates et al (2015). The technical details of the process by which this field is interpolated onto a Cartesian grid are discussed in Prior and Yeates (2016a).…”
Section: Generating the Magnetic Fieldmentioning
confidence: 99%